Development of proposals for improving the functioning of a family farm in a heterogeneous business environment - Termosa, Iryna (Technology audit and production reserves, 2020)
The research object is the process of creating a family milk farm and its activity efficiency. One of most important requirements as to family milk farm functioning is a possibility to provide high-quality milk production that its functioning efficiency and recoupment of investments for its creation depend on. A place of family farms as small economic subjects is determined on an example of the total entrepreneurial environment of Ukraine. The scheme of the organizational-economic functioning of family farms, created on the base of rural house economies, is proposed. The dynamics of milk and milk products production and also the dynamics of prices for milk of different sort are determined. Based on conducted studies, the expedience for creating additional production capacities in the field of milk production for industrial processing is substantiated. Actual requirements as to milk quality regulation are studied. At the research there are used means of system modeling for calculating the efficiency of family milk farm functioning. There are determined Quality parameters, influencing the economic efficiency of milk production at a family farm. They include: real fat share and real protein share in milk. For realizing the calculation of the parameters for the effective milk-good production by a family milk farm, there is proposed an economic-mathematical model of its creation by two variants: minimal and optimal. Due to this model, it is possible to calculate a minimal and maximal sum of investments, and also a period of their recoupment. Comparing with analogous well-known methods, the proposed approaches allow to determine production parameters of a family farm, to determine a sum of investments, to calculate a period of their recoupment.